LubForLife: more reliable and cost competitive VTOL electro-mechanical equipment, from multidisciplinary sizing to tribology impacts to lower cost of operation - D'Andrea, M.; Guidi, G.; Malleret, F. (My University, 2021)
Re-lubrication of Electro-mechanical actuators (EMA) is synonymous with aircraft downtime, mobilising resources, increased aircraft operating costs and higher risk of fault conditions caused by human error. With the challenging task of eliminating re-lubrication during the entire electro-mechanical actuator operating life, UMBRAGROUP is leading a Research & Technology (R&T) project, called LubForLife, in collaboration with academics and industrial partners. This R&T project seeks to achieve more realistic results by addressing the needs of a real flight-control actuator based upon requirements set with one of the major airframer who is closely associated with the project and milestones. In this paper, UMBRAGROUP lists all the key design aspects identified as drivers for a ball screw based EMA and focuses, then, on some main aspects linked to tribology, architecture and configuration, laying the foundations for the definition of a new standard for electromechanical actuators with no maintenance tasks or very limited ones